Mortality and Causes of Death in Patients Requiring VEPTR Surgery. Issue 1 (April 2016) - Smith, John; Heflin, John; Vitale, Michael; Samdani, Amer; Morgan, Jessica; ,
Introduction: The VEPTR device is used to treat a heterogeneous population of children with EOS and TIS. Complications associated with this treatment are known to be high, but there is limited documentation regarding risk of mortality in this population while undergoing treatment. The objective of this study is to report the 14 year mortality and cause of death from 4 major centers treating patients with TIS. This is a retrospective review of patients treated at 4 institutions for EOS and TIS. All patients were treated or had planned treatment with VEPTR instrumentation. Methods: 295 consecutive patients with EOS treated with VEPTR between 2000 and 2014 were reviewed. All patients were entered into a prospectively collected database. For the patients who died during or awaiting treatment, medical records were reviewed to determine the age and cause of death. Results: 292 patients treated with VEPTR and 3 patients awaiting surgery were included. 17 patients died during the study period, for an overall mortality rate of 5.76%. The etiology was varied in the patients who died (congenital/structural-1; neuromuscular-8; syndromic-5; idiopathic-3). There were 1261 total VEPTR-related procedures completed. Causes of death included: respiratory failure-8; shunt complications-2; cardiac failure-4; and GI complications-3. Two children died of pulmonary and nutritional complications while awaiting surgery. One patient died of a cardiac arrhythmia in the operating room. Conclusion: EOS occurs in a complex heterogeneous group of children and is associated with multiple co-morbidities. The 2010 combined mortality rate for children 1–19 years of age was 54.1/100, 000 while the rate for this group was 823.2/100, 000 suggesting the long term natural history of this condition is associated with significantly increased mortality. While the aggressive surgical management of EOS compared with the natural history is not debated, there is clearly a need for a better understanding of the mortality risk over time for this patient population.